PENYIDIKAN TERHÐDÐP TINDAK PIDANA PEMBUKÐÐN LÐHÐN DENGÐN CÐRÐ MEMBÐKÐR (Studi di KepolisiÐ°n Resor KÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t) - Dwiki Julio Dharmawan (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Dwiki Julio Dharmawan Fakultas Hukum Universitas Brawijaya Email: dwikijulio28@gmail.com Â ABSTRAK Penulis memilih temÐ° tersebut dilÐ°tÐ°r belÐ°kÐ°ngi berdÐ°sÐ°rkÐ°n dÐ°tÐ° rekÐ°pitulÐ°is penÐ°ngÐ°nÐ°n kÐ°sus lingkungÐ°n pÐ°dÐ° tingkÐ°t dÐ°erÐ°h kÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t, penegÐ°kÐ°n hukum lingkungÐ°n dengÐ°n menggunÐ°kÐ°n sÐ°rÐ°nÐ° hukum pidÐ°nÐ° mÐ°sih belum berhÐ°sil. KÐ°renÐ° sedikitnyÐ° jumlÐ°h kÐ°sus pidÐ°nÐ° lingkungÐ°n yÐ°ng dÐ°pÐ°t diselesÐ°ikÐ°n. BerdÐ°sÐ°rkÐ°n hÐ°l tersebut diÐ°tÐ°s, kÐ°ryÐ° tulis ini mengÐ°ngkÐ°t rumusÐ°n mÐ°sÐ°lÐ°h : (1) BÐ°gÐ°imÐ°nÐ° reÐ°lisÐ°si penyidikan oleh KepolisiÐ°n Resor KÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t terhÐ°dÐ°p tindak pidana pembukÐ°Ð°n lÐ°hÐ°n dengÐ°n cÐ°rÐ° membÐ°kÐ°r di KÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t? (2) ÐpÐ° kendÐ°lÐ° penyidikan oleh KepolisiÐ°n Resor KÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t terhÐ°dÐ°p tindak pidana pembukÐ°Ð°n lÐ°hÐ°n dengÐ°n cÐ°rÐ° membÐ°kÐ°r di KÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t? Metode penulisan penulis menggunakan metode pendekÐ°tÐ°n yuridis empiris, yÐ°kni dengÐ°n menyelesÐ°ikÐ°n permÐ°sÐ°lÐ°hÐ°n yÐ°ng Ð°kÐ°n dibÐ°hÐ°s, berdÐ°sÐ°rkÐ°n perÐ°turÐ°n-perÐ°turÐ°n yÐ°ng berlÐ°ku sertÐ° di hubungkÐ°n kenyÐ°tÐ°Ð°n yÐ°ng telÐ°h terjÐ°di di mÐ°syÐ°rÐ°kÐ°t. DÐ°ri hÐ°sil pembahasan yang diperoleh bÐ°hwÐ° reÐ°lisÐ°si penyidikan oleh KepolisiÐ°n Resor KÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t terhÐ°dÐ°p tindak pidana pembukÐ°Ð°n lÐ°hÐ°n dengÐ°n cÐ°rÐ° membÐ°kÐ°r di KÐ°bupÐ°ten KotÐ°wÐ°ringin BÐ°rÐ°t dÐ°lÐ°m penyidikan pihÐ°k KepolisiÐ°n menggunÐ°kÐ°n PÐ°sÐ°l 187 dÐ°n 188 KUHP, PÐ°sÐ°l 108 UndÐ°ng-UndÐ°ng No 32 TÐ°hun 2009 TentÐ°ng PerlindungÐ°n dÐ°n PengelolÐ°Ð°n LingkungÐ°n Hidup, dÐ°n menggunÐ°kÐ°n PerÐ°turÐ°n DÐ°erÐ°h No 5 tÐ°hun 2003 TentÐ°ng PengendÐ°liÐ°n KebÐ°kÐ°rÐ°n HutÐ°n dÐ°n LÐ°hÐ°n. KemudiÐ°n dÐ°lÐ°m penyidikan terhÐ°dÐ°p tindak pidana pembukÐ°Ð°n lÐ°hÐ°n dengÐ°n cÐ°rÐ° membÐ°kÐ°r pihÐ°k KepolisiÐ°n bekerjÐ° sÐ°mÐ° dengÐ°n Penyidik PegÐ°wÐ°i Negeri Sipil (PPNS) dÐ°lÐ°m penyidikÐ°n untuk menemukÐ°n pelÐ°ku. Dalam penyidikan pihak kepolisian mengalami kendala-kendala sehingga pihak kepolisian kesulitan dalam penyidikan. KÐ°tÐ° Kunci: Penyidikan, Tindak Pidana, PembukÐ°Ð°n lÐ°hÐ°n, MembÐ°kÐ°r ABSTRACT Based on recapitalised data concerning environmental management in the Regency of West Kotawaringin, law enforcement of environment through criminal law has not shown any success. This is indicated by the fact that there were only fewer cases that managed to be settled. From the issue mentioned, this research is mainly aimed to study (1) how enquiries over land clearance by burning are delivered by Sub-regional Police Department in the Regency of West Kotawaringin, and (2) what factors impede the enquiries by the Police Department in West Kotawaringin concerning land clearance by burning. This research was conducted based on empirical juridical method, where issues discussed are settled according to existing regulations before the issues are related to what happens in society. The research finds that the enquiries over burning land for clearance refer to Article 187 and 188 of Criminal Code, Article 108 of Act Number 32 of 2009 concerning Environmental Protection and Management, and Local Regulation Number 5 of 2003 concerning Control of Forest and Land Fire. The enquiries were delivered by the police together with Civil Servants assigned as Enquirers to reveal the culprit. However, there are still some obstacles hampering the process of enquiries by the police. Keywords: enquiry, criminal offense, land clearance, burning